Hemodynamic Assessment of Pregnant People with and without Obesity by Noninvasive Bioreactance: A Pilot Study - Figueiro-Filho, Ernesto A.; Robinson, Na T. S.; Carvalho, Jose; Keunen, Johannes; Robinson, Monique; Maxwell, Cynthia (American Journal of Perinatology Reports, 2022)
Objective This study aimed to identify cardiovascular differences between pregnant people with and without obesity for trimester-specific changes in hemodynamic parameters using noninvasive cardiac output monitoring (NICOM).Study Design This study is a pilot prospective comparative cohort between pregnant people with and without obesity. Hemodynamic assessment was performed with NICOM (12–14, 21–23, and 34–36 weeks) during pregnancy.Results In first trimester, pregnant people with obesity had higher blood pressure, stroke volume (SV), total peripheral resistance index (TPRI), and cardiac output (CO). Pregnant people with obesity continued to have higher SV and cardiac index (second and third trimesters). During the first trimester, body mass index (BMI) positively correlated with SV, TPRI, and CO. Fat mass showed a strong correlation with TPRI. BMI positively correlated with CO during the second trimester and fat mass was positively associated with CO. During the third trimester, TPR negatively correlated with BMI and fat mass.Conclusion Fat mass gain in the period between the first and second trimesters in addition to the hemodynamic changes due to obesity and pregnancy contribute to some degree of left ventricular diastolic dysfunction which was manifested by lower SVs. Future work should investigate the possible causative role of obesity in the cardiovascular changes identified in people with obesity.
Keywords: pregnancy; noninvasive cardiac output monitoring; obesity; hemodynamic; pilot study